2019
DOI: 10.1016/j.heliyon.2019.e02068
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of reactive textile dye Novacron Super Black G by free cells of newly isolated Alcaligenes faecalis AZ26 and Bacillus spp obtained from textile effluents

Abstract: Bacteria were isolated from effluents of textile industries and screened by their capability to decolorize at least one of eight reactive dyes used in the textile industries. Three isolates having the capability to decolorize the highest number of dyes with more than 25% of decolorization were identified as Alcaligenes faecalis AZ26, Bacillus cereus AZ27 and Bacillus sp. AZ28 based on morphological, cultural, biochemical characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Gulati and Jha isolated two bacterial strains from dye effluent contaminated the soil with degrading ability of Reactive Blue 19 dye, up to 95% after 72 hr in optimum conditions (Gulati & Jha, ). Hossen et al, have similar results and indicated that the decolorization of NSB‐G dye by the three bacterial isolates was almost saturated (∼90%) after 72 hr of incubation (Hossen et al, ).…”
Section: Resultsmentioning
confidence: 71%
“…Gulati and Jha isolated two bacterial strains from dye effluent contaminated the soil with degrading ability of Reactive Blue 19 dye, up to 95% after 72 hr in optimum conditions (Gulati & Jha, ). Hossen et al, have similar results and indicated that the decolorization of NSB‐G dye by the three bacterial isolates was almost saturated (∼90%) after 72 hr of incubation (Hossen et al, ).…”
Section: Resultsmentioning
confidence: 71%
“…Although good results are achieved in terms of reducing the chemical oxygen demand (COD) and decolorization, usually these values are for dye concentration that does not exceed the 200 mg L –1 , and as was shown earlier dye concentration in real textile wastewater can reach until 800 mg L –1 . In addition, it should be noted that reactor volumes in many cases are small ( Valli Nachiyar et al, 2016 ; Abd El-Rahim et al, 2017 ; Hossen et al, 2019 ; Zahran et al, 2019 ). As an example, Hossen et al (2019) studied the decolorization efficiency of different strains in simulated effluents, some of which reached efficiencies of even 90%.…”
Section: Regarding Biological Treatmentsmentioning
confidence: 99%
“…The 16S rDNA sequencing analysis has been used, and the authors concluded bacterial isolate TS20 was the most predominant bacteria species for color removal. Hossen et al (2019) investigated the remediation of Novacron Super Black G dye (NSB-G) using three bacteria isolates (Bacillus sp. AZ28, Bacillus cereus AZ27, and Alcaligenes faecalis AZ26) from textile effluent.…”
Section: Bacteria or Bacterial Processesmentioning
confidence: 99%
“…Hossen et al (2019) investigated the remediation of Novacron Super Black G dye (NSB‐G) using three bacteria isolates ( Bacillus sp. AZ28, Bacillus cereus AZ27, and Alcaligenes faecalis AZ26) from textile effluent.…”
Section: Biological Processesmentioning
confidence: 99%